Plastic Waste Conversion over a Refinery Waste Catalyst - Vollmer, Ina; Jenks, Michael J. F.; Mayorga González, Rafael; Meirer, Florian; Weckhuysen, Bert M. (Angewandte Chemie International Edition, 2021)
Polypropylene (PP) makes up a large share of our plastic waste. We investigated the conversion of PP over the industrial Fluid Catalytic Cracking catalyst (FCC‐cat) used to produce gasoline from crude oil fractions. We studied transport limitations arising from the larger size of polymers compared to the crude oil‐based feedstock by testing the components of this catalyst separately. Infrared spectroscopy and confocal fluorescence microscopy revealed the role of the FCC matrix in aromatization, and the zeolite Y domains in coking. An equilibrium catalyst (ECAT), discarded during FCC operation as waste, produced the same aromatics content as a fresh FCC‐cat, while coking decreased significantly, likely due to the reduced accessibility and activity of the zeolite domains and an enhanced cracking activity of the matrix due to metal deposits present in ECAT. This mechanistic understanding provides handles for further improving the catalyst composition towards higher aromatics selectivity. On the path to finding better catalysts for polyolefin plastic waste conversion to aromatics, we have found that a waste refinery catalyst performed better than the fresh catalyst with decreased accumulation of deactivating carbonaceous deposits. Fluorescence microscopy and vibrational spectroscopy has been used to elucidate the interaction of the polymer with the catalyst and to map the location and type of bulky aromatic species.